THE ROLE OF THE TEACHER AS A MENTOR TO STIMULATE STUDENTS ABILITIES IN FIQH LESSONS AT MA MUHAMMADIYAH 6 KOTANOPAN AFTER COVID-19 PANDEMIC - Siti Holidah; Munawir Pasaribu (Proceeding International Seminar of Islamic Studies, 2022)
In the world of education, teachers must always pay attention to the abilities of students both online and offline, especially in learning fiqh such as worship, muamalah, Mawaris, jinayah and others. However, due to the COVID-19 pandemic, which made the government issue a circular regarding the policy of the learning process from face to face to online or learning from home, it made students' interest in learning decline so that MAM 6 kotanopan students did not understand Fiqh subjects which were usually practiced directly but at the same time. pandemic students only get material in theory. At this time, the government has implemented face-to-face learning, although it has not been fully effective and is still complying with health protocols. This study aims to determine how the teacher's role is to improve students' ability to understand fiqh learning. The method used in this research is descriptive qualitative method using data collection techniques such as observation, interviews, documentation with the subject of class XII fiqh teachers and several students. The results of this study indicate that the teacher's role in fiqh subjects has contributed significantly to the procedures for worship and the practice of various religious activities studied in the discussion material.Keywords: Role, teacher, learning, fiqh